LEKSEM GOLEK ‘MENCARI’ DALAM BAHASA JAWA - Alfelia Nugky Permatasari (Sekolah Vokasi Universitas Gadjah Mada, 2019)
Every language in the world is the primary tool for its speakers to communicate with each other. Each language has its own uniqueness so that no language is more special than others. One of its uniqueness that is worth to discuss is a large number of lexemes one language has, while other languages only have a small number of vocabularies to explain a particular concept. This study focuses on the lexeme in Javanese language with 'to search' as the core meaning. The number of lexemes that are generally represented by the word golek‘to search’ include: njala, ngarit,mancing, etc. This study aims to show the differences between them by looking at the meaning components possessed by the lexemes. The data in forms of lexemes were obtained by using introspection method. The meaning of these lexemes then was ascertained with the help of dictionaries and interviews with other Javanese native speakers. Structural semantic analysis theory by Nida (1975) was used to analyze the meaning of those lexemes. The usage of lexemes in sentences were used to show the differences between lexemes, especially those with the same meaning components. From at least fifteen lexemes with 'to search' as its core meaning found in Javanese language, there are six dimensions of meaning that distinguish them. The six include, SOURCE OF POWER, OBJECT, OWNERSHIP, INTEREST, PLACE, and SUBJECT. Although some of the lexemes have similar components of meaning in several dimensions of meaning, there are still differences in meaning components between the lexemes. This reinforces the opinion that no two words are absolute synonyms or have exactly the same meaning.